Stoichiometric and physiological mechanisms that link hub traits of submerged macrophytes with ecosystem structure and functioning. (1st September 2021) - Rao, Qingyang; Su, Haojie; Ruan, Linwei; Deng, Xuwei; Wang, Lantian; Rao, Xiao; Liu, Jiarui; Xia, Wulai; Xu, Pengke; Shen, Hong; Chen, Jun; Xie, Ping
Highlights: Field and experiment data were used to detect the hub traits of submerged macrophytes. Organ P, starch, and total nonstructural carbohydrate contents were hub traits. Ecosystems dominated by more homeostatic and C-rich communities were more productive. High litter quality induced by eutrophication implied faster nutrient cycling rates. Abstract: Eutrophication strongly influences plant stoichiometric characteristics and physiological status by altering nutrient and light availability in the water column. However, the mechanisms linking plant functional traits with ecosystem structure and functioning to clarify the decline of submerged macrophytes have not been fully elucidated to date. Therefore, based on a field investigation of 26 macrophytic shallow lakes on the Yangtze Plain, we first constructed a plant trait network at the whole-plant level to determine the hub traits of submerged macrophytes that play central regulatory roles in plant phenotype. Our results suggested that organ (leaf, stem, and root) phosphorus (P), starch, and total nonstructural carbohydrate (TNC) contents were hub traits. Organ starch and TNC were consistent with those in the experiment-based network obtained from a three-month manipulation experiment. Next, the mechanisms underlying the relationships between the hub traits and vital aspects of ecological performance were carefully investigated using field investigation data. Specifically, stoichiometric homeostasis of P ( H P ), starch, and TNC were positively associated with dominance and biomass at the species level, and community biomass at the community level. Additionally, structural equation modeling clarified not only a hypothesized pathway from eutrophication to water clarity and community TNC, but also combined effects of community TNC and H P on community biomass. That is, ecosystems dominated by more homeostatic communities tended to have more carbon (C)-rich compounds in relatively oligotrophic conditions, which promoted the primary production of macrophytes. Eutrophication was determined to affect community structure by inhibiting the predominance of more homeostatic species and the production of carbohydrates. Finally, reduced community biomass and increased nutrient contents and nutrient:C ratios in plants induced by eutrophication implied a decrease in the C sink in biomass and may potentially lead to an enhancement of litter decomposition rates and nutrient cycling rates. By adjusting plant responses to eutrophication, stoichiometric and physiological mechanisms linking plant traits with ecosystem structure have important implications for understanding ecosystem processes, and these results may contribute to practical management to achieve the restoration of submerged macrophytes and ecosystem services. Graphical abstract: Image, graphical abstract